Structure and physical properties of NiO/Co3O4 nanoparticles - Naseri, Mahmoud Goodarz; Dehzangi, Arash; Mohamed Kamari, Halimah; See, Alex; Abedi, Mina; Salasi, Reza; Golikand, Ahmad Nozad; Dianat, Pouya; Larki, Farhad; Abedini, Alam; Hassan, Jumiah; Far, Ahmad Kamalian; et al. (MDPI, 2016)
The thermal treatment method was employed to prepare nickel-cobalt oxide (NiO/CO3O4) nanoparticles. This method was attempted to achieve the higher homogeneity of the final product. Specimens of nickel-cobalt oxide were characterized by various experimental techniques, including X-ray diffraction (XRD), transmission electron microscopy (TEM) and Fourier transform infrared spectroscopy (FTIR). X-ray diffraction results showed that there was no crystallinity in the predecessor, and it still had the amorphous phase. The formations of the crystalline phases of the nickel-cobalt oxide nanoparticles started from 350–500 °C, and the final products had different crystallite sizes ranging from 11–35 nm. Furthermore, the variation of DC conductivity (σdc), impedance, tangent loss (tgδ) and dielectric constant (εʹ) of the calcined specimens with frequency in the range of 102–106 Hz was investigated. σdc showed a value of 1.9 × 10-6 S/m, 1.3 × 10-6 S/m and 1.6 × 10-6 S/m for the specimens calcined at 350, 400 and 450 °C, respectively. Additionally, a decrease in tgδ values with an increase in temperature was observed. Finally, the formed nanoparticles exhibited ferromagnetic behaviors, which were confirmed by using a vibrating sample magnetometer (VSM).